Differences in heart rate reserve of similar physical activities during work and in leisure time – A study among Danish blue-collar workers - Coenen, P.; Korshøj, M.; Hallman, D.; Huysmans, M.; van der Beek, A.; Straker, Leon; Holtermann, A. (Elsevier Inc., 2018)
© 2018 Elsevier Inc. Recent studies suggest that while leisure-time physical activity (LTPA) promotes general health, engaging in occupational physical activity (OPA) may have negative health consequences. It has been hypothesized that the different health effects from OPA and LTPA can be explained by differences in physical activity (PA) intensity in these two domains. To assess the intensity of OPA and LTPA, we aimed to study the percentage heart rate reserve (%HRR) during similar types of OPA and LTPA during workdays. Data from the NOMAD study on Danish blue-collar workers (n = 124) with objective measurements of PA (using accelerometers) and heart rate (using heart rate monitors) for 4 workdays were analysed. Activities of sitting, standing, moving, walking, and stair climbing were identified and %HRR in each of these activities was determined for work and leisure. %HRR was significantly higher during OPA than LTPA. These differences were more pronounced in men than in women. Although not statistically significant in the fully adjusted model, we found indications that these differences were more pronounced in those with low compared to high fitness. To our knowledge, this is the first study with objective measurements showing that %HRR is higher during the same gross-body postural activities when performed at work compared to leisure-time during workdays. This elevated intensity may help explaining the negative health consequences of engagement in high levels of OPA. Future guidelines should distinguish OPA from LTPA, possibly by advising workers to remain active during their leisure time, in particular when they are highly active at work.